2000
DOI: 10.1080/00498250050078039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of celecoxib metabolism and excretion in mouse, rabbit, dog, cynomolgus monkey and rhesus monkey

Abstract: 1. The metabolism and excretion of celecoxib, a specific cyclooxygenase 2 (COX-2) inhibitor, was investigated in mouse, rabbit, the EM (extensive) and PM (poor metabolizer) dog, and rhesus and cynomolgus monkey. 2. Some sex and species differences were evident in the disposition of celecoxib. After intravenous (i.v.) administration of [14C]celecoxib, the major route of excretion of radioactivity in all species studied was via the faeces: EM dog (80.0%), PM dog (83.4%), cynomolgus monkey (63.5%), rhesus monkey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 6 publications
(3 reference statements)
1
23
0
Order By: Relevance
“…given to four animals to obtain the corresponding doseresponse. The doses were chosen in the therapeutic range from preliminary pharmacokinetic data, eicosanoid profiles, and current literature (20)(21)(22)(23). For instance, celecoxib was administered at higher doses because it has a larger volume of distribution and is less efficacious when compared with rofecoxib.…”
Section: Methodsmentioning
confidence: 99%
“…given to four animals to obtain the corresponding doseresponse. The doses were chosen in the therapeutic range from preliminary pharmacokinetic data, eicosanoid profiles, and current literature (20)(21)(22)(23). For instance, celecoxib was administered at higher doses because it has a larger volume of distribution and is less efficacious when compared with rofecoxib.…”
Section: Methodsmentioning
confidence: 99%
“…Still, no glucuronide conjugate metabolites of lefucoxib were found. It was reported that the metabolic pathway for celecoxib, another selective inhibitor of COX-2, involved oxidation of the aromatic methyl group to form a hydroxy metabolite, which underwent additional oxidation to a carboxylic acid metabolite in rats [13]. Another study reported that carboxylic acid metabolite of celecoxib could be determined by HPLC-UV [14], which was tried and thought to be helpful in detecting carboxylic acid metabolites of lefucoxib if they existed.…”
Section: Discussionmentioning
confidence: 97%
“…COX-2 is induced at inflammation sites [31,32] but is also found constitutively in brain, spinal cord, kidney and some other tissues [33][34][35]. Clinical studies indicate that celecoxib is metabolised in the liver via the oxidative pathway to the corresponding alcohol and carboxylic acid and is removed by renal excretion as a glucuronide metabolite [36]. The chemical structures of celecoxib, hydroxycelecoxib, and carboxycelecoxib are shown in Fig.…”
Section: Celecoxibmentioning
confidence: 97%